PERUBAHAN KONDISI SOSIAL EKONOMI MASYARAKAT PASCA PEMBANGUNAN JEMBATAN SITI NURBAYA (Studi Kasus: Kelurahan Batang Arau Kecamatan Padang Selatan Kota Padang) - Dahnil, Dahnil; Prahara, Surya; Elfemi, Nilda (Pendidikan Sosiologi, 2014)
Thesis examines the socio-economic changes after the construction of the Bridge Siti Nurbaya (Case Study: Batang Arau Village Padang Selatan Urban District City of Padang), namely social interaction, social behavior and education as well as changes in livelihood and income levels. The goal is achieved in this study was to describe: "Socio-Economic Conditions Society Changing at Development". The theory used is the Theory of Social Change Neil Smelser. Changes to the existing range Smelser is a separate process, as well as the process of social units that were formed specifically think (Long, 1987:162). Informants research taken by purposive sampling. Informants in the study of 20 people, consisting of sub-district staff and the community in the village of Batang Arau which utilizes Siti Nurbaya Bridge as a place to trade. This type of data is the primary data derived from interviews with informants and secondary data obtained from the relevant references. Data were collected through observations, interviews and documentation. Data analysis was performed with data reduction techniques, the presentation of the data and draw conclusions. These results indicate that: 1) the social condition before Bridge Siti Nurbaya built, people have a good attitude and behavior, good manners and mutual respect, but with the construction of the Siti Nurbaya bridge result in changes to behavior, attitudes and education community. More individualized society, the lack of respect and passion for the decline in mutual cooperation, while public education is progressing with a number of children through education and (2) the economic condition of the people of Batang Arau Village before the bridge Siti Nurbaya, including employment and income poor, after the construction of bridge Siti Nurbaya economic conditions cause changes Batang Arau Village community, opening jobs, livelihood began to grow and increase revenues. People who switched livelihood and some even have two jobs and increased revenue on a new livelihood.